The Influence of Cultural Intelligence on Network Capability and Branch Performances, With Mediation of Entrepreneurial Orientation and Market Orientation - Laksana, Yohanes Pamungkas Jati; Widjaja, Anton Wachidin (Ekonomis: Journal of Economics and Business, 2025)
This study explores the impact of cultural intelligence on network capability, focusing on how entrepreneurial orientation and market orientation, contribute to branch performance. This research uses a quantitative survey with outlet heads across Indonesia. This survey examines the relationship between cultural intelligence and branch performance, while interviews provide insights into entrepreneurial orientation and market orientation that influence network capability. This study found that cultural intelligence has a positive impact on branch performance, entrepreneurial orientation and market orientation. Leaders who utilize cultural aspects play a role in motivating employee to observe the culture of their surrounding environment where they work, which is oriented towards entrepreneurship. Entrepreneurial orientation and market orientation enhance the success of network development capabilities. These findings may not be fully generalizable to other companies or cultural contexts. This study contributes to the literature on network capability by highlighting the importance of cultural intelligence in banking institutions. The research extends the theories of entrepreneurial orientation and market orientation by applying them to the context of corporate network capability.